دور الضوء الطبيعي في صناعة الفراغ المعماري "ديناميكية الفراغ" - قصاب, أحمد سعيد; بدر, رنا; خلاص, محمد (Latakia University Journal -Engineering Sciences Series, 2019)
The need for light is an urgent human need, so this light controls the shape of the human day (Daylight through natural light "The sun with its direct interaction, Broken and penetrated…etc." and Night through natural light "In its forms and its multiple features and objectives"). Light reflects itself as a decisive factor in architecture in general (External façade configuration and internal functional spaces). However, bringing lighting to the building goes beyond merely lighting the place, Due to the ability of light to influence the characteristics of the lighted space, light has become a design tool that can control many of the characteristics of the space to belit. This is a fact that one finds in any design that realizes this fact, whether in a traditional building or as the embodiment of the famous La Corbusier "Beautiful shapes gathered in light" ان الحاجة إلى الضوء هي حاجة إنسانية ملحة، حيث يتحكم هذا الضوء بشكل اليوم البشري (النهار عبر الضوء الطبيعي "الشمس بتفاعلها المباشر والمنكسر والمخترق...الخ" والليل عبر الضوء الطبيعي "بأشكاله وملامحه المتعددة وأهدافه"). ويعبر الضوء عن نفسه كعامل حاسم في العمارة بشكل عام (التشكيل الواجهي الخارجي والفراغات الداخلية الوظيفية)، حيث أن جلب الإضاءة للبناء يتجاوز مجرد إضاءة الفراغ. فنظراً لقدرة الضوء على التأثير في خصائص الفراغ المضاء أصبح الضوء أداة تصميم بإمكانه أن يتحكم في كثير من صفات الفراغ المراد أضاءته، وهذه حقيقة يجدها المرء في أي تصميم يدرك هذه الحقيقة سواء كان في بناء تقليدي أو كتجسيد لمقولة لوكوربوزييه الشهيرة: "العمارة هي أشكال جميلة جمعت في الضوء".